#TITLE_ALTERNATIVE# - SUKMA WINDRATIH (NIM : 13613063), PRAMESTHI
This final report presents some parts of the research in developing of Flight Laboratory that will be utilized to enrich flight mechanics teaching in the Faculty of Mechanical Engineering and Aerospace Engineering in Bandung Institute of Technology. Specifically, this report presents the development of Graphical User Interface (GUI) using Matlab, which can be used by students to analyze stability of aircraft. To demonstrate the use and capability of this GUI, a flight test simulation is performed in X-Plane for Cessna 172 aircraft. The flight data is transmitted by X-Plane using User Datagram Protocol, and received by Simulink routinely, then passed through to the GUI. The simulation results will be shown in a graph that depicts real time aircraft data, the longitudinal static stability parameters, and the neutral point of the aircraft,and related simulated data that can be saved in the excel file. The result of this research is GUI which can be used to analyze longitudinal static stability, simulation scenario of flight testing Cessna 172 aircraft that is declared static longitudinally stable with neutral point value is 21.1 inch from default X-Plane, and analysis of ability and error that occur in GUI design.